2011
DOI: 10.1080/13506285.2011.594459
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing visual working memory encoding: The role of target novelty

Abstract: Perceptual salience improves the encoding of information into visual working memory (WM). However, the factors that contribute to this facilitation effect are not well understood. This study tested the influence of target familiarity on WM encoding. In each trial, participants were presented with either one or three targets and asked to encode their locations into WM. In Experiment 1, target familiarity was manipulated by presenting either an upright (familiar target) or upside-down (unfamiliar/novel target) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 79 publications
(131 reference statements)
6
28
0
Order By: Relevance
“…Novel stimuli thus attract attention, also when there is no incentive to pay attention to them, and even when performance on ongoing tasks suffers. Consistent with novel stimuli attracting attention, novel stimuli are encoded better into visual working memory than familiar ones (Mayer et al, 2011(Mayer et al, , 2014. Mayer and colleagues suggested that this effect was mediated by more efficient allocation of attentional resources to novel than to familiar items, rather than to low-level stimulus characteristics.…”
Section: Attention To Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…Novel stimuli thus attract attention, also when there is no incentive to pay attention to them, and even when performance on ongoing tasks suffers. Consistent with novel stimuli attracting attention, novel stimuli are encoded better into visual working memory than familiar ones (Mayer et al, 2011(Mayer et al, , 2014. Mayer and colleagues suggested that this effect was mediated by more efficient allocation of attentional resources to novel than to familiar items, rather than to low-level stimulus characteristics.…”
Section: Attention To Noveltymentioning
confidence: 99%
“…Recent findings in humans suggest that novelty elicits a wide range of additional effects on cognition. For example, novelty can strengthen reward processing Guitart-Masip et al, 2010), drive exploration Krebs et al, 2009), facilitate encoding of visual working memory (Mayer et al, 2011), enhance perception (Schomaker and Meeter, 2012), and speed up responses . Animal studies have shown that exploration of a novel environment promotes longterm potentiation (LTP) in the hippocampus, thereby improving memory encoding (Davis et al, 2004;Li et al, 2003;Sajikumar and Frey, 2004;Sierra-Mercado et al, 2008;Straube et al, 2003a).…”
Section: Introduction: Novelty's Effects On Cognitionmentioning
confidence: 99%
“…The selection process allows limiting of processing to items that are salient and currently relevant in order to deal with the limited capacity of WM. Recent evidence suggests that both bottom-up cues based on perceptual stimulus features and top-down cues driven by expectations, knowledge, and current goals, can increase the salience of the items to be encoded and facilitate visual WM performance in healthy participants (Fine & Minnery, 2009; Mayer, Kim, & Park, 2011; Schmidt, Vogel, Woodman, & Luck, 2002; Vogel, McCollough, & Machizawa, 2005). PSZ are also able to use simple and salient visual cues to select relevant information for WM encoding (Gold et al, 2006; Smith, Eich, Cebenoyan, & Malapani, 2011) and WM encoding improves when the task involves perceptually salient targets (Lee & Park, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that deficits in early-stage visual processing (Badcock, Badcock, Read, & Jablensky, 2008; Hartman, Steketee, Silva, Lanning, & McCann, 2003; Javitt, Liederman, Cienfuegos, & Shelley, 1999; Javitt et al, 1997; Tek et al, 2002) and/or higher-level cognitive processes associated with the consolidation process itself (Fuller, Luck, McMahon, & Gold, 2005; Fuller et al, 2009) can lead to abnormal encoding in schizophrenia (for a review see Haenschel & Linden, 2011). Moreover, attentional processes can modulate the encoding process (Fine & Minnery, 2009; Mayer et al, 2011; Vogel, McCollough, & Machizawa, 2005) and might be impaired in PSZ (Gold, Fuller, Robinson, Braun, & Luck, 2007; Hahn et al, 2010; Luck & Gold, 2008; Tanaka et al, 2007). Thus, difficulties in selecting relevant information or deploying attention to the relevant feature efficiently (Nestor et al, 1992; Posner, Early, Reiman, Pardo, & Dhawan, 1988; Sereno & Holzman, 1996) may result in imprecise encoding or in encoding wrong stimuli which then may lead to increased false memory responses.…”
mentioning
confidence: 99%
“…We cannot exclude that if circles and squares differed in perceptual salience, this could have confounded the effect of WM load. However, given that perceptual salience is encoded very fast (in the range of tenths of ms) (e.g., Nothdurft, 2002; Mayer et al, 2011; Wolfe, 1998) and the targets were presented rather long (2 s), a potential salience effect might be disregarded. …”
mentioning
confidence: 99%